Establishment of safety power range and subsequent commutation failure suppression strategy for hybrid cascaded HVDC system - He Wang; Jiazhi Guo; Jing Bian; Guoqing Li; Tuo Wang (International Journal of Electrical Power & Energy Systems)
The hybrid cascaded high-voltage direct current (HC-HVDC) system integrates the benefits of both LCC and MMC technologies. However, the inverter LCC is prone to suffer subsequent commutation failure (SCF) when an AC fault occurs. Therefore, a coordinated control strategy (CCS) based on the safety power range (SPR) is proposed in this paper. Firstly, the adverse effects of electrical quantity fluctuation and LCC’s reactive power demand on system recovery under different control modes are analyzed. Then, considering the role of the controller and MMC dynamic reactive power support, the SPR model is established under the coupling of multiple electrical quantities. Secondly, to realize the coordination of SCF suppression and rapid power recovery, a CCS based on the MMC’s reactive power outer loop and the LCC’s voltage-dependent current order limiter (VDCOL) is proposed by analyzing the power operating points in SPR. Finally, based on PSCAD/EMTDC, simulations and comparative analysis are conducted under different fault conditions. The findings demonstrate that the suggested approach can not only effectively suppress SCF, but also significantly increase power transmission, and the active power increase is up to 129 %, thus having a certain value for engineering applications.